SMS Banking in Saudi Arabia - Abdullah, Alsaab Saif (2009)
Banking has always been a highly information intensive activity particularly over the last few decades that information and Communication technology (ICT) has affected the banking industry heavily. The appearance of SMS banking services has changed the nature of financial services delivery costumers. One of the most growing phenomenons in financial services is mobile internet banking. The purpose of this study is explorer the adoption of SMS banking among Saudi customers, an emerging Middle East economy in the area. The present study modifies the technology acceptance model and applies it to banks customers in Saudi Arabia. By providing SMS banking services, banks can get notable cost saving, reduce their branch networks, and improve efficiency. But since customers do not adopt and use these service, banks cannot profit from them. A numbers of Saudi banks recently have started to offer SMS banking services to their customers, but the fact it got a respectable reaction from people’ point of view. A model of TAM with factors from perceived innovation attributes and the personal characteristics of adopters have been developed to identify the most factors that influence SMS banking adoption among Saudi customers. The result of this study were contribute were positively related to SMS banking adoption as hypothesized. The positive association between combination among all independent variables (ease of use, usefulness, credibility, compatibility and observability) was supported.